Factors Militating against the Implementation of Nomadic Education in the South-South Geo-Political Zone of Nigeria - Edoho, G. E.; Bassey, R. O.; Nkanga, I. I.; Asor, L. J. (Journal of Research in Adult and Continuing Education, 2025)
The National Commission for Nomadic Education (NCNE) was established in 1989 to address the stark educational inequities experienced by nomadic populations in Nigeria. Nomadic education in Nigeria was designed to provide access to quality education for pastoralists, migrant farmers, and fisher-folk whose mobile livelihoods exclude them from conventional schooling. This paper reviewed and discussed scholars opinions that ranges from education as empowerment, structural and operational weaknesses, socio cultural perspectives, contemporary concerns of climate change and global comparative insights, functions of national commission for nomadic education were also highlighted, factors militating against the implementation of nomadic education in the South-South geo-political zone of Nigeria were reviewed and lastly, the objectives of nomadic education programme were also discussed. Literatures reviewed reveal that despite significant policy commitments, implementation is undermined by multiple factors which is why it was recommended that predictable financing, livelihood-sensitive curricula, teacher incentive schemes, mobile and ICT-enabled learning strategies, and stronger community participation should be considered. It concludes that without targeted and context-sensitive reforms, nomadic education in the South-South will remain aspirational rather than transformative.